Rapid and Precise Mobile Data Processing for Fire Brigades and Rescue Services (SAFeR/GÜTER/SHARE) - Koch, Rainer; Harnasch, Rüdiger; Lee, Bo-Sik; Pottebaum, Jens (Human Interface and the Management of Information. Interacting in Information Environments, Symposium on Human Interface 2007, Held as Part of HCI International 2007, Beijing, China, July 22-27, 2007, Proceedings, Part II)
Keywords: Ver{\

Actin-dependent regulation of connective tissue growth factor - Muehlich, Susanne; Cicha, Iwona; Garlichs, Christoph D.; Krueger, Bettina; Posern, Guido; Goppelt-Struebe, Margarete (American Journal of Physiology-Cell Physiology)
Expression of connective tissue growth factor (CTGF) in endothelial cells is modulated by shear stress affecting the organization of the cytoskeleton. The molecular connection between alterations of actin and CTGF expression was investigated in human umbilical vein endothelial cells (HUVEC) and a microvascular endothelial cell line. Overexpression of nonpolymerizable monomeric actin R62D interfered with stress fiber formation in HUVEC and concomitantly reduced immunoreactive CTGF. In microvascular endothelial cells, flow-dependent upregulation of CTGF was prevented by this actin mutant. In contrast, overexpression of actin S14C strengthened filamentous actin and increased CTGF expression. These data indicated an inverse relationship between CTGF expression and monomeric actin. Coexpression of the mutant actins and different CTGF promoter constructs revealed an actin-sensitive site between 3 and 4.5 kb of the CTGF promoter. A CArG-like box at -3791 bp was responsible for actin-dependent CTGF induction as shown by mutagenesis. Overexpression of actin S14C activated the nonmutated promoter significantly more strongly than the mutated promoter. Actin polymerization is regulated by the small GTPase RhoA and activation of serum response factor (SRF). Overexpression of constitutively active RhoA or SRF significantly increased CTGF protein synthesis. The 4.5-kb promoter construct, but not the construct with a mutation in the CArG box, was activated by SRF or RhoA, providing evidence for a functional role of this site in CTGF induction. These findings provide novel evidence that monomeric actin is the connecting link between alterations in the cytoskeleton and CTGF gene expression and demonstrate the importance of SRF in regulating CTGF transcription.

Efficient Operation in Sensor and Actor Networks Inspired by Cellular Signaling Cascades - Dressler, Falko; Dietrich, Isabel; German, Reinhard; Krueger, Bettina (1st ACM/ICST International Conference on Autonomic Computing and Communication Systems (Autonomics 2007))
The investigation and the development of self-organizing systems are especially needed for operation and control in massively distributed systems such as Sensor and Actor Networks (SANETs). The main issues addressed by self-organization techniques are scalability, network lifetime, and real-time support. In the literature, biological principles are often cited as inspirations for technical solutions, especially in the domain of self-organization. This concept already resulted in a good number of solutions with significant impact such as ant-based routing and immune system inspired network security solutions. In this paper, another specific biological field is investigated: cellular signaling cascades for event-specific reaction initiated by individual cells in collaboration with their direct neighbors. Information between cells are transmitted via proteins and result in the cascade of protein–protein or protein–DNA interactions to produce a specific cellular answer, e.g. the activation of cells or the transmission of mediators. These processes are programmed in every individual cell and lead to a coordinated reaction on a higher organization platform. We transferred these mechanisms to operation and control in SANETs. In particular, a rule-based processing scheme relying on the main concepts of cellular signaling cascades has been developed. It is relying on simple local rules and providing problem specific reaction such as local actuation control and data manipulation. We describe this Rule-based Sensor Network (RSN) technology and demonstrate comparative simulation results that show the feasibility of our approach.

Adaptive Data Dissemination in Sensor Networks using WPDD - Dressler, Falko; German, Reinhard; Krueger, Bettina (IEEE Frontiers in the Convergence of Bioscience and Information Technologies (FBIT 2007))
In Wireless Sensor Networks (WSNs), address-based routing approaches often lead to severe problems due to node mobility, energy-saving sleep-cycles, and often missing or unreliable address information. Data-centric routing schemes such as flooding or gossiping solve these problems but may lead to congestion or starvation. Based on biologically inspired mechanisms known from cellular signaling pathways, we discovered potentials in enhancing the communication required for self-organization in network environments suffering from data paths with low reliability and time variations of the reliability. Using an importance factor for particular transmissions in combination with feedback loops, the overall quality of the global system can be increased. The resulting algorithm, Weighted Probabilistic Data Dissemination (WPDD), includes an inherent adaptation to changing network conditions. Congestion control is supported as well as prioritized data communication. This paper outlines the working behavior of WPDD and demonstrates its applicability based on selected simulation results.

Interdisziplinäre Kommunikation zwischen den ‚zwei Kulturen' - Weber, Jutta (Journal Netzwerk Frauenforschung NRW Nr. 22/2007)

Methodische Entwicklung von Echtzeit 3D-Anwendungen für Schulung und Präsentation - Wortmann, Raphael

Position-based Routing Strategies - Rührup, Stefan

Urinary C-peptide excretion in free-living healthy children is related to dietary carbohydrate intake but not to the dietary glycemic index. - Buyken, Anette; Kellerhoff, Y; Hahn, S; Kroke, A; Remer, T (J Nutr)

Rapid growth among term children whose birth weight was appropriate for gestational age has a longer lasting effect on body fat percentage than on body mass index. - Karaolis-Danckert, N; Buyken, Anette; Bolzenius, K; Perim de Faria, C; Lentze, MJ; Kroke, A (Am J Clin Nutr)

The influence of habitual protein intake in early childhood on BMI and age at adiposity rebound: results from the DONALD Study - Günther, A L B; Buyken, Anette; Kroke, A (International Journal of Obesity)

REVIS – Reform der Ernährungs- und Verbraucherbildung in Schulen - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Zur Analyse von Unterrichtsmaterialien für die Ernährungs- und Verbraucherbildung - Methfessel, B.; Schlegel-Matthies, Kirsten (Haushalt & Bildung)

A fast k-means implementation using coresets - Frahling, Gereon; Sohler, Christian (Proceedings of the twenty-second annual symposium on Computational geometry - SCG '06)
In this paper we develop an efficient implementation for a k-means clustering algorithm. Our algorithm is a variant of KMHybrid [28, 20], i.e. it uses a combination of Lloyd-steps and random swaps, but as a novel feature it uses coresets to speed up the algorithm. A coreset is a small weighted set of points that approximates the original point set with respect to the considered problem. The main strength of the algorithm is that it can quickly determine clusterings of the same point set for many values of k. This is necessary in many applications, since, typically, one does not know a good value for k in advance. Once we have clusterings for many different values of k we can determine a good choice of k using a quality measure of clusterings that is independent of k, for example the average silhouette coefficient. The average silhouette coefficient can be approximated using coresets.To evaluate the performance of our algorithm we compare it with algorithm KMHybrid [28] on typical 3D data sets for an image compression application and on artificially created instances. Our data sets consist of 300,000 to 4.9 million points. We show that our algorithm significantly outperforms KMHybrid on most of these input instances. Additionally, the quality of the solutions computed by our algorithm deviates less than that of KMHybrid.We also computed clusterings and approximate average silhouette coefficient for k=1,…,100 for our input instances and discuss the performance of our algorithm in detail.

Design and Construction of a 3D-Scanning-Laservibrometer - Becker, C; Wedman, S; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Interaktive 3D-Visualisierung multidimensionaler Datensätze - Lindner, M.; Goetz, F.; Weise, R.; Fricke, H.; Burchert, W.; Domik, Gitta

Pizza, Pasta und Döner Kebab: Mediterranean Dishes in the Everyday Life of German Young People - Bartsch, Silke; Methfessel, Barbara; Schlegel-Matthies, Kirsten (Mediterranean Food. Concepts and Trends. Proceedings of the 15th International Ethnological Food Research Conference, Dubrovnik, 27 September - 3 October)

Pizza, Pasta, Döner Kebab - Mittelmeerkost im Alltag deutscher Jugendlicher. Historische und soziale Hintergründe - Schlegel-Matthies, Kirsten; Methfessel, Barbara; Bartsch, Silke (Haushalt & Bildung)

Mittelmeerkost im Alltag deutscher Jugendlicher - Ein Lehr-Forschungsprojekt mit Studierenden in Heidelberg und Paderborn - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Haushalt & Bildung)

Zur Entwicklung eines Kerncurriculums für den Lernbereich „Arbeitslehre" - Philipps, U.; Bigga, Regine (Haushalt & Bildung)

Dynamische Kantenextraktion: Ein Verfahren zur Generierung von Tracking-Informationen für Augmented Reality-Anwendungen auf Basis von 3D-Referenzmodellen - Matysczok, Carsten